THE ROLE OF AQUACULTURE AND INNOVATIVE BIOTECHNOLOGIES IN THE REPRODUCTION AND CONSERVATION OF AQUATIC BIOLOGICAL RESOURCES - Rakhmatova S. M.; Davlatova M. J. (Modern American Journals, 2025)
The article explores the significance of aquaculture and innovative biotechnologies in the reproduction and conservation of aquatic biological resources. With increasing global demand for fish and seafood products, the pressure on natural ecosystems is rapidly growing, leading to the depletion of many aquatic species and the degradation of water environments. Aquaculture, as a sustainable alternative to traditional fishing, provides opportunities to reduce the burden on natural stocks while ensuring food security. The research emphasizes how advanced technologies, including genetic selection, bioengineering, nanotechnology, and bioremediation, are transforming aquaculture practices and making them more efficient and environmentally friendly.
Keywords: Aquaculture, biotechnologies, aquatic biological resources, conservation, reproduction, sustainable development, biodiversity, food security, genetic selection, recirculating aquaculture systems.